A Phasor Estimation Algorithm Based on Iterative Filtering to Remove the Decaying Direct Current Component - Pengcheng Xiang; Dengwei Duan; Xiaokun Zhao; Xiantao Zhang; Xilu Zheng; Hang Zou; Jike Wu; Xueying Liu (IEEE Access)
With the large-scale use of power electronic devices, the alternating current side of the system produces decaying direct current components, greatly reducing the performance of the phasor estimation algorithms. To address this problem, this paper presents a phasor estimation algorithm based on sinc interpolation. First, an equivalent cosine model is proposed to simulate the dynamic characteristics of the decaying direct current component. Second, based on the boundary conditions, the optimal frequency band of the equivalent cosine model is determined iteratively to reconstruct the decaying direct current component. Last, the phasor form of the components to be measured is modeled via sinc interpolation, and the phasor parameters are obtained via least squares. In the simulation, the accuracy of the equivalent cosine model is improved by 319.56% compared with that of the traditional method. The proposed algorithm satisfies the accuracy requirement of 1% total vector error in the protection class phasor measurement unit framework.